2016
DOI: 10.1080/00958972.2016.1193169
|View full text |Cite
|
Sign up to set email alerts
|

Air-stable fluorescent primary phosphine complexes of molybdenum and tungsten

Abstract: Here we report a study on the reactivity of the fluorescent air-stable primary phosphine 8-((4-phosphino)phenyl)-4,4-dimethyl-1,3,5,7-tetramethyl-2,6-diethyl-4-bora-3a,4a-diaza-s-indacene 4 with [Mo (CO) 6 ], [W(CO) 6 ], [Mo(CO) 4 (piperidine)] and [W(CO) 4 (piperidine)] which yields the mono-phosphine [Mo(CO) 5 (4)] 5, [W(CO) 5 (4)] 6 and di-phosphine cis-[Mo(CO) 4 (4) 2 ] (7) and cis-[W(CO) 4 (4) 2 ] (9) complexes as the predominant products. In addition to the characterisation of these complexes by multinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Higham and co-workers suggested that the observations for rhodium complexes could be explained if the PCH 2 CH 2 group in phosphiranes, because of the pyramidalized structure and increased s-character of the donor orbitals, was a poorer σ-donor than PMe 2 . , A similar rationalization is plausible for the Mo complexes. In contrast, no difference in the CO stretching frequencies for W­(CO) 5 complexes was observed. , However, this system is particularly insensitive to phosphine structure, so that electronic differences among PPh 3 , PMe 3 , and the mixed arylmethylphosphines PPh 3– n Me n ( n = 0–3) could not be determined by vibrational spectroscopy …”
Section: Resultsmentioning
confidence: 99%
“…Higham and co-workers suggested that the observations for rhodium complexes could be explained if the PCH 2 CH 2 group in phosphiranes, because of the pyramidalized structure and increased s-character of the donor orbitals, was a poorer σ-donor than PMe 2 . , A similar rationalization is plausible for the Mo complexes. In contrast, no difference in the CO stretching frequencies for W­(CO) 5 complexes was observed. , However, this system is particularly insensitive to phosphine structure, so that electronic differences among PPh 3 , PMe 3 , and the mixed arylmethylphosphines PPh 3– n Me n ( n = 0–3) could not be determined by vibrational spectroscopy …”
Section: Resultsmentioning
confidence: 99%
“…KOAc and NaOAc were also applied as ionic additives in the Hirao reaction [ 58 - 62 ]. In the presence of Pd(OAc) 2 or Pd(dba) 2 as the Pd precursor, dppf [ 58 - 65 ], dppb [ 58 , 66 - 70 ], dppp [ 58 ] and BINAP [ 58 ] could also be used as ligands. Pd(dppf) 2 Cl 2 was also a suitable catalyst to promote the coupling reaction of dialkyl phosphites [ 71 , 72 ].…”
Section: The Traditional Hirao Reactionmentioning
confidence: 99%